Identification of critical factors to system performance using availability modeling and simulation analysis - Hussin, H. (2014)
Availability analysis presents a means to understand the impact of existing maintenance system and maintenance resources to the overall system operational availability. The practical method for conducting availability analysis of a plant system at operation phase is illustrated and discussed via a case study of an acid gas removal system of gas processing plant. This study demonstrates that the availability modeling and simulation is effective in assessing the existing and future system configurations and determining possible impacts and critical factors to systems availability. These findings can significantly assist management to make right actions in improving plant system performances. Â© (2014) Trans Tech Publications, Switzerland.